A systematic review: metabolomics-based identification of altered metabolites and pathways in the skin caused by internal and external factors - Masutin, Viktor; Kersch, Christian; Schmitz-Spanke, Simone (Experimental Dermatology, 2022)
The skin's ability to function optimally is affected by many diverse factors. Metabolomics has a great potential to improve our understanding of the underlying metabolic changes and the affected pathways. Therefore, the objective of this study was to review the current state of the literature and to perform further metabolic pathway analysis on the obtained data. The aim was to gain an overview of the metabolic changes under altered conditions and to identify common and different patterns as a function of the investigated factors. A cross-study comparison of the extracted studies from different databases identified 364 metabolites, whose concentrations were considerably altered by the following factor groups: irradiation, xenobiotics, ageing and skin diseases (mainly psoriasis). Using metabolic databases and pathway analysis tools, the individual metabolites were assigned to the corresponding metabolic pathways and the most strongly affected signalling pathways were identified. All factors induced oxidative stress. Thus, antioxidant defence systems, especially coenzyme Q10 (ageing) and the glutathione system (irradiation, ageing, xenobiotics), were impacted. Lipid metabolism was also impacted by all factors studied. The carnitine shuttle as part of β-oxidation was activated by all factor groups except ageing. Glycolysis, Krebs (TCA) cycle and purine metabolism were mainly affected by irradiation and xenobiotics. The pentose phosphate pathway was activated, and Krebs cycle was downregulated in response to oxidative stress. In summary, it can be ascertained that mainly energy metabolism, lipid metabolism, antioxidative defence and DNA repair systems were impacted by the factors studied.
CRIS-Team Scopus Importer:2022-02-11